The Impact of Brand trust, Self-image Congruence and Usage Satisfaction toward Smartphone Repurchase Intention - Goh, See Kwong; Jiang, Nan; Tee, Pei Leng (International Review of Management and Marketing, 2016)
The purpose of this study is to examine the subjective factors; brand trust, self-image congruence and usage satisfaction toward repeat purchase intention of smartphones among the Gen-Y consumers in Malaysia. A total of 182 respondents participated in this research. Most of the respondents purchased a smartphone within the last 12 months and a large number of the respondents are active users of text messaging and smartphone applications. Results indicate that self-image congruence is the main antecedents for repeat purchase of smartphones. This is the followed by usage satisfaction as the second predictor and lastly would be brand trust. This paper provides some discussion and recommendations for practitioners. Keywords: brand trust, self-image, satisfaction, smartphones, Malaysia JEL Classifications: M310, M370